Addressing Methodological and Generalizability Challenges in Cervical Rotation-Traction Manipulation (CRTM) for Cervical Radiculopathy [Letter] - Wang R; Xv M; Yao L (Journal of Pain Research)
Ruixue Wang,1 Mingzhu Xv,2 Lin Yao3 1Innovation Research Institute of Traditional Chinese Medicine, Shandong University of Traditional Chinese Medicine, Jinan, 250355, People’s Republic of China; 2Shandong University of Traditional Chinese Medicine, Jinan, 250355, People’s Republic of China; 3Institute of Acupuncture and Moxibustion, Shandong University of Traditional Chinese Medicine, Jinan, 250355, People’s Republic of ChinaCorrespondence: Lin Yao, Changqing Campus, Shandong University of Traditional Chinese Medicine, No. 4655 University Road, Guyun Lake Street, Changqing District, Jinan, Shandong, People’s Republic of China, Email yaolin@sdutcm.edu.cn